Gingivitis en niños que reciben terapia antiasmática con beta2 agonistas adrenérgicos. Estudio comparativo - Basauri Esteves, Rosa Leonor (2008)
With the purpose to determine if the gingivitis in children that receive therapy antiasmatic with beta2 agonistas adrenergic, it increases their occurrence and then to propose a preventive intervention, one studies all these the children that went to the clinic of Pediatrics of Trujillo's Educational Regional Hospital among November 1 the 2006 and 30 of November of the 2007. The study type was descriptive, traverse and comparative The sample in a total of 351 children, it was conformed by 117 children with use of beta2 agonistas adrenergic inhaled with corticoids, 117 children with use of beta2 agonistas adrenergic inhaled without corticoids and 117 children with use of beta2 agonistas not inhaled adrenergic. The obtained results show that the gingivitis frequency is bigger in the children than they use beta2 agonistas inhaled adrenergic with corticoids that it was 82.9%, in those inhaled without corticoids it was 36.8% and with use of not inhaled it was 43.6%. The gingivitis grade in the children that use beta2 agonistas adrenergic inhaled with corticoids was light the same as in those with use of having inhaled without corticoids and in those with use of not inhaled. As for the comparison of gingivitis frequency in children with antiasmatic treatment that use beta2 agonistas adrenergic inhaled with corticoids it is significantly superior that in those that use beta2 agonistas inhaled without corticoids and that in those that use beta2 not inhaled agonistas.